The Ameliorating Effect of Artificial Coffee from Mangrove Fruits (Rhizophora mucronata) on T Lymphocyte Cells and Renal Histopathology of BALB/c Mice Induced by Lipopolysaccharide - Cahyono, Eko; Tanod, Wendy Alexander; Ijong, Frans Gruber; Ansar, Novalina Maya Sari; Mandeno, Jefri Anthonius; Karimela, Ely John; Rieuwpassa, Frets Jonas; Palawe, Jaka Frianto Putra; Sambeka, Yana; Setiawati, Natalia Prodiana (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
The potential of Rhizophora mucronata mangrove fruits as antioxidants is noteworthy, with promising prospects as nutraceuticals, particularly in their role as immunomodulators for T lymphocyte cells. R. mucronata fruits have been utilized by household industries in Indonesia as a coffee-like drink (artificial coffee). This study aims to determine the ability of mangrove fruit artificial coffee R. mucronata to stimulate T lymphocyte cells and renal histopathology conditions in LPS-induced mice animal models. This study also characterizes proximate characteristics, antioxidant capacity, and Gas Chromatography-Mass Spectrometry (GC-MS) screening of mangrove fruit artificial coffee compounds. The stages of this research included the process of mangrove fruit artificial coffee; analysis of proximate and caffeine; compounds screening (GC-MS) and toxicity prediction (Pro-Tox II); antioxidant capacity (DPPH); T lymphocyte cell expression (flow cytometry); and renal histopathological evaluation. The results showed moisture content (5.22±0.20%); ash (5.17±0.27%); protein (13.74±0.24%); fat (11.63±0.32%); carbohydrate (64.23±0.15%), caffeine (1.09±0.04%). GC-MS analysis showed that the compounds contained in artificial coffee were derivatives of fatty aldehyde, fatty acid, and cycloalkanes compound classes. Predicted toxicity of artificial coffee LD50 5000 mg/kg. Antioxidant capacity is classified as moderate (IC50 119.41±0.99µg/mL). Mangrove fruit artificial coffee can increase the relative number of CD4+CD62L+ by 14.68-29.48% and CD8+CD62L+ T lymphocyte cells by 12.60-30.33%. Artificial coffee can also increase the number of healthy cells and reduce the cells that undergo necrosis in the renal of LPS-induced mice. This study concluded that mangrove fruit artificial coffee R. mucronata positively affects T lymphocyte activation and mice renal cells’ protection from necrosis due to LPS induction.